2011
DOI: 10.1007/s11242-011-9741-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rotation on the Onset of Double Diffusive Convection in a Sparsely Packed Anisotropic Porous Layer

Abstract: The effect of rotation on the onset of double diffusive convection in a sparsely packed anisotropic porous layer, which is heated and salted from below, is investigated analytically using the linear and nonlinear theories. The Brinkman model that includes the Coriolis term is employed for the momentum equation. The critical Rayleigh number, wavenumber for stationary and oscillatory modes and a dispersion relation are obtained analytically using linear theory. The effect of anisotropy parameters, Taylor number,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…For example Capone and Gentile [80] presented sharp stability results in a rotating anisotropic porous layer subject to lack of local thermal equilibrium (LaLotheq, LTNE). Double diffusive convection in a rotating anisotropic porous layer was presented by Galkwad and Kouser [81], Malashetty and Heera [82], and Malashetty and Begum [83]. Double diffusive convection in a rotating porous medium saturated with a coupled stress fluid was considered by Malashetty et al [84], while double diffusive convection in a rotating porous layer saturated by a viscoelastic fluid was investigated by Kumar and Bhadauria [85].…”
Section: Additional Effects On Flow and Natural Convection In Rotatinmentioning
confidence: 99%
“…For example Capone and Gentile [80] presented sharp stability results in a rotating anisotropic porous layer subject to lack of local thermal equilibrium (LaLotheq, LTNE). Double diffusive convection in a rotating anisotropic porous layer was presented by Galkwad and Kouser [81], Malashetty and Heera [82], and Malashetty and Begum [83]. Double diffusive convection in a rotating porous medium saturated with a coupled stress fluid was considered by Malashetty et al [84], while double diffusive convection in a rotating porous layer saturated by a viscoelastic fluid was investigated by Kumar and Bhadauria [85].…”
Section: Additional Effects On Flow and Natural Convection In Rotatinmentioning
confidence: 99%
“…Malashetty and Gaikwad (2001) have studied the effect of cross diffusion terms on double diffusive convection in a porous medium in the presence of horizontal gradients. Malashetty and Begum (2011) have investigated the effect of rotation on the onset of double diffusive convection in a sparsely packed anisotropic porous layer. Recently Gaikawad andKamble (2012a, 20121b, 2014) have investigated theoretically the double diffusive convection in a fluid saturated anisotropic couple stress fluid and porous layer in the presence of Soret and rotational effect.…”
Section: Introductionmentioning
confidence: 99%
“…21 in porous layer. 22,23 The mixed convection through a parallel-plate vertical porous channel, which was assumed to be hydrodynamically anisotropic, was studied by Degan and Vasseur. 16 They found that for Da < 10 -5 the viscous effects near the boundaries were negligible, and the permeability ratio and inclination of principal axes of permeability had a strong influence on the thermal convection.…”
Section: Introductionmentioning
confidence: 99%